From ligands to binding motifs and beyond; the enhanced versatility of nanocrystal surfaces. Issue 34 (27th July 2016) - De Roo, J.; De Keukeleere, K.; Hens, Z.; Van Driessche, I.
Abstract : Surface chemistry bridges the gap between nanocrystal synthesis and their applications. Abstract : Surface chemistry bridges the gap between nanocrystal synthesis and their applications. In this respect, the discovery of complex ligand binding motifs on semiconductor quantum dots and metal oxide nanocrystals opens a gateway to new areas of research. The implications are far-reaching, from catalytic model systems to the performance of solar cells.